Classifying The Shape Of Aggregate Using Hybrid Multilayered Perceptron Network. - Joret, Ariffuddin; Mat Isa, Nor Ashidi; Ali, Ahmad Nazri; Zamli, Kamal Zuhairi; Azizli, Khairun Azizi; M Al Batah, M Subhi (2005)
In concrete production, shape of aggregate reflects the quality of concrete produced. The well-shaped aggregates are said to produce high quality concrete by reducing water to cement ratio. On the contrary, poor-shaped aggregates often require higher water to cement ratio in concrete production.